Gaya Kepemimpinan Laissez Faire Kepala Sekolah dalam Peningkatan Prestasi Belajar Siswa di SMP Al-Furqon Boarding School Cimerak - Dian Herdiana; Sobirin Sobirin; Asep Saepurrohman (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
The laissez-faire leadership style is one of the leadership styles implemented at SMP Al-Furqon Boarding School Cimerak, characterized by granting extensive freedom to teachers and students to make decisions and manage their own teaching and learning activities. On one hand, the freedom given to teachers and students can encourage innovation in the teaching and learning process. However, on the other hand, the lack of supervision and guidance from the school principal can lead to a lack of coordination in the learning process. The purpose of this research is to determine 1) how the laissez-faire leadership style of the principal at Al-Furqon Boarding School Cimerak is, and 2) how the students' academic performance at Al-Furqon Boarding School Cimerak is. The type of research used in this study is qualitative. The data collection techniques used are observation, interviews, and documentation. The subjects in this study are the Principal, Teachers, Staff, and also Students of Al-Furqon Boarding School. The data analysis technique in this research involves data collection, data reduction, data presentation, and final conclusions. The validity of the data in this study is tested using triangulation techniques. The results of the research indicate that 1) the leadership style of the school principal employs a laissez-faire leadership style, which allows teachers to try new things in learning. The principal only receives information and does not monitor specific data regarding student progress. 2) Students' academic performance improved because the teaching staff was given the freedom to create learning programs both inside and outside the classroom. Students are able to achieve good performance based on the assessments conducted daily up to the final semester exam. The habit of studying before exams and the use of report cards as a motivational tool also play an important role in enhancing students' enthusiasm for learning.